2017
DOI: 10.1007/s40618-017-0792-x
|View full text |Cite
|
Sign up to set email alerts
|

Gemigliptin, a novel dipeptidyl peptidase-IV inhibitor, exerts a synergistic cytotoxicity with the histone deacetylase inhibitor PXD101 in thyroid carcinoma cells

Abstract: Our results demonstrate that gemigliptin induces cytotoxicity in thyroid carcinoma cells. Moreover, gemigliptin has a synergistic activity with PXD101 in the induction of cell death through involvement of Bcl2 family proteins, xIAP and survivin as well as mediation of Akt and AMPK in thyroid carcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…PI3K/AKT signaling orchestrates many intracellular processes essential for survival of healthy cells (29). In thyroid carcinoma cells, it has been shown that aberrant activation of PI3K/AKT signaling participates in neoplastic transformation, and PI3K/AKT signaling plays pivotal roles in cell survival in our previous reports (30)(31)(32)(33)(34)(35)(36)(37). With respect to the involvement of PI3K/AKT signaling in evodiamineinduced antitumor action, it has been shown that evodiamine enhances the therapeutic efficacy of gemcitabine via direct or indirect negative regulation of PI3K/AKT signaling in in vitro and in vivo models of pancreatic cancer (12).…”
Section: Discussionmentioning
confidence: 94%
“…PI3K/AKT signaling orchestrates many intracellular processes essential for survival of healthy cells (29). In thyroid carcinoma cells, it has been shown that aberrant activation of PI3K/AKT signaling participates in neoplastic transformation, and PI3K/AKT signaling plays pivotal roles in cell survival in our previous reports (30)(31)(32)(33)(34)(35)(36)(37). With respect to the involvement of PI3K/AKT signaling in evodiamineinduced antitumor action, it has been shown that evodiamine enhances the therapeutic efficacy of gemcitabine via direct or indirect negative regulation of PI3K/AKT signaling in in vitro and in vivo models of pancreatic cancer (12).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, survivin is related to chemoresistance and unfavorable prognosis in patients with malignant tumors, and overexpression of survivin is relevant to dedifferentiation and progression in thyroid cancer (19,28). In this respect, we reported that expression of survivin was associated with survival of thyroid carcinoma cells (21)(22)(23)(24)(25)(26). Survivin is stimulated through PI3K/AKT signaling in response to cytokines, growth factors and chemotherapeutic agents in malignant cells (29).…”
Section: Discussionmentioning
confidence: 96%
“…thyroid carcinoma cells (21)(22)(23)(24)(25)(26). Although the PDZ-LIM family protein LMP-1 was shown to inhibit cell death by regulating PI3K/AKT signaling in nasal natural killer/T-cell lymphoma cells (11), the participation of PI3K/AKT signaling in pro-survival effect of enigma in thyroid carcinoma cells has not been evaluated before.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing HDAC6 in a therapeutic manner is accompanied by less severe adverse effects compared to class I HDACs. The great therapeutic window is The difluoromethyl-1,3,4-oxadiazole (DFMO) moiety was reported in 2017 twice in patents by Lee et al [31] and Kim et al [32] as a potent and selective HDAC6 inhibitor moiety and has recently been studied in detail by Cellupica et al [33] and König et al [34] and evaluated and applied by Keuler et al [35], Onishi et al [36] and Ptacek et al [37]. HDAC6 is particularly interesting because of its unique substrate scope related to nononcological conditions.…”
Section: 34-oxadiazolesmentioning
confidence: 99%